Efektivitas Modalitas Stimulasi Elektroterapi Terhadap Pemulihan Pasien Pasca Stroke: Literatur Review - Hafizh Ammar Kusuma; Dini Nur Alpiah (JURNAL ILMIAH NUSANTARA, 2026)
One of the leading causes of long-term disability is stroke, which impacts motor function impairment, spasticity, balance, and decreased ability to perform functional activities. One way to maximize functional recovery and patient independence in post-stroke rehabilitation is by using electrotherapy stimulation modalities. The purpose of this literature review is to evaluate the effectiveness of various electrotherapy stimulation methods on the recovery of patients who have experienced stroke. Literature research on the use of transcutaneous electrical nerve stimulation (TENS), neuromuscular electrical stimulation (NMES), transcutaneous electrical acupoint stimulation (TEAS), and transcutaneous auricular vagus nerve stimulation (taVNS) was used in the writing methodology. The results showed that electrotherapy stimulation improves motor function, reduces spasticity, increases functional activities, and improves the quality of life of post-stroke patients. The results suggest that this modality can be used as an additional component of post-stroke patient rehabilitation programs. Electrotherapy stimulation can be used both alone or in combination with conventional therapy.